Composite Nanoparticles

By mixing titanium oxide nanoparticles with yttrium compound, highly transparent, colorless and active composite nanoparticles under dark light were prepared, which solved the problems of insufficient activity and poor transparency of titanium oxide nanoparticles in the prior art, and achieved the preparation of high-efficiency nanoparticles suitable for antibacterial and antiviral materials.

JP7669167B2Active Publication Date: 2025-04-28OSAKA GAS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021060697
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-04-28
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

In the prior art, titanium oxide nanoparticles have insufficient mobility and poor transparency when irradiated with ultraviolet light, and synthesis of tantalum oxide nanoparticles is difficult.

Method used

By mixing titanium oxide nanoparticles with yttrium compounds, yttrium-containing composite nanoparticles were prepared, and antibacterial and antiviral materials with high transparency, colorlessness and activity in dark light were prepared.

Benefits of technology

The high transparency and low color of yttrium compound nanoparticles are achieved, and these composite nanoparticles remain active in dark light, which is suitable for the preparation of efficient antibacterial and antiviral materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To readily synthesize a nanoparticle comprising a lanthanum compound having high transparency and less coloration; and to prepare an antibacterial-antiviral material having high transparency, free of coloration, and showing activity even at a dark place by using the lanthanum compound.SOLUTION: A composite nanoparticle comprises a lanthanum compound and a titania nanoparticle.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composite nanoparticles. [Background technology]

[0002] Titania nanoparticles have various properties as photocatalysts, such as superhydrophilization, hydrogen production, deodorization by decomposing organic matter, and antibacterial effects (Non-Patent Document 1). However, titania nanoparticles have the disadvantage that they require ultraviolet light irradiation to be activated and are basically inactive in the dark.

[0003] Photocatalysts that are active without the need for UV light irradiation to activate titania nanoparticles have also been developed, but such titania nanoparticles have problems such as lack of transparency and coloration.

[0004] Lanthanum is a rare earth element, and unlike ordinary metal oxides, it is not colored, and many lanthanum compounds are also colorless. Lanthanum carbonate is sometimes used as a medicine, has the ability to adsorb phosphorus, and is highly safe.

[0005] However, the synthesis of lanthanum oxide from lanthanum salts requires harsh conditions: for example, lanthanum oxide is produced by calcining lanthanum nitrate at 600 °C.

[0006] Lanthanum oxide is also produced by reacting lanthanum salts in a liquid phase reaction, such as the solvothermal method and glycothermal treatment. The synthesis of lanthanum oxide at 300°C, the limit temperature of lanthanum oxide, is usually sufficient to produce metal oxide nanoparticles from metal salts. However, the reaction stops at the intermediate structures of lanthanum oxide, such as hydroxide and salt.

[0007] For this reason, it is difficult to synthesize lanthanum oxide nanoparticles using conventional techniques (Non-Patent Documents 2 to 4). [Prior art documents] [Non-patent literature]

[0008] [Non-Patent Document 1] Hiroshi Irie, and Kazuhito Hashimoto. "Current status and future development of photocatalytic technology." Materia 41.4 (2002): 242-246. [Non-Patent Document 2] Akutsu, D. et al. "High activity of lanthanum oxide-based catalysts for oxidative coupling of methane." Bulletin of the Faculty of Engineering, Saitama Institute of Technology 26 (2016): 19-24. [Non-Patent Document 3] Hiroshi Konan et al. "Formation of lanthanum diacetate monohydroxide by heat treatment of lanthanum acetylacetonate dihydrate in organic solvents containing a small amount of water." Journal of the Ceramic Society of Japan 107.1247 (1999): 682-685. [Non-Patent Document 4] Masashi Inoue, et al. "Special feature: Technologies supporting the synthesis of inorganic materials and their evaluation" Formation of La(CH3COO)2(OH) by glycothermal treatment of lanthanum acetate 1.5 hydrate and its thermal decomposition behavior." Journal of the Chemical Society of Japan 10 (1991): 1254-1260. Summary of the Invention [Problem to be solved by the invention]

[0009] The conventional techniques described above have problems with titania, such as activity and transparency when not irradiated with ultraviolet light, and problems with lanthanum, such as the difficulty of synthesizing nanoparticles.

[0010] Therefore, an object of the present invention is to easily synthesize nanoparticles containing a lanthanum compound that are highly transparent and have little coloration.

[0011] Another object of the present invention is to use the lanthanum compound to obtain an antibacterial and antiviral material that is highly transparent, colorless, and active even in the dark. [Means for solving the problem]

[0012] Means of the Invention In view of the above object, the present inventors conducted extensive research and discovered that by mixing titania nanoparticles with a lanthanum compound, nanoparticles containing lanthanum can be obtained, thereby solving the above problem.

[0013] After further research, the present invention was completed.

[0014] That is, the present invention includes the following configurations.

[0015] Section 1. A composite nanoparticle, Lanthanum compounds, and Titania nanoparticles, containing Composite nanoparticles.

[0016] Section 2. The content of the lanthanum compound is 1% by mass to 25% by mass in terms of lanthanum atoms relative to the titania nanoparticles. Item 1. The composite nanoparticle according to item 1.

[0017] Section 3. The titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface, Specific surface area is 70m 2 / g or more, 3. The composite nanoparticle according to item 1 or 2.

[0018] Section 4. When the titania nanoparticles are heated to 600°C using a thermogravimetric and differential thermal analyzer, the weight loss at 200°C or higher is 5% by mass or more. 4. The composite nanoparticle according to any one of items 1 to 3.

[0019] Section 5. The titania nanoparticles have an average particle size of 30 nm or less. 5. The composite nanoparticle according to any one of items 1 to 4.

[0020] Section 6. A method for producing composite nanoparticles, comprising the steps of: The composite nanoparticles contain a lanthanum compound and a titania nanoparticle, The method includes a step of mixing titania and a lanthanum compound in a solvent containing at least water. Manufacturing method.

[0021] Section 7. The lanthanum compound is at least one lanthanum compound selected from the group consisting of lanthanum (III) acetate, lanthanum (III) acetate 1.5-hydrate, lanthanum (III) carbonate, lanthanum (III) carbonate octahydrate, lanthanum (III) oxide, lanthanum (III) nitrate, and lanthanum (III) nitrate hexahydrate; Item 7. The method for producing the same according to item 6.

[0022] Section 8. A deodorant, antibacterial, and / or antiviral material, Contains a lanthanum compound and titania nanoparticles, The titania nanoparticles have an average particle size of 30 nm or less. Deodorizing, antibacterial and / or antiviral materials.

[0023] Section 9. Further comprising at least one metal selected from the group consisting of silver, copper, platinum, and zinc; 9. The deodorizing, antibacterial, and / or antiviral material according to item 8.

[0024] Section 10. An antiviral coating solution, The deodorizing, antibacterial, and / or antiviral material according to claim 8 or 9, and Contains water Antiviral coating liquid. Effect of the Invention

[0025] According to the present invention, nanoparticles containing a lanthanum compound that are highly transparent and have little coloring can be easily synthesized.

[0026] According to the present invention, by mixing titania nanoparticles with a lanthanum compound, composite nanoparticles which contain lanthanum uniformly, have high transparency, and are little colored can be easily obtained.

[0027] According to the present invention, by using composite nanoparticles containing the lanthanum compound, it is possible to obtain an antibacterial and antiviral material that is highly transparent, colorless, and active even in the dark. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] In this specification, the term "containing" is a concept that encompasses all of "comprise," "consist essentially of," and "consist only of."

[0029] In this specification, when a numerical range is expressed as A to B, it indicates A or more and B or less.

[0030] In this specification, "titanium oxide" or "titania" refers to titanium dioxide (TiO 2 ), but also refers to titanium trioxide (Ti 2 O 3 );Titanium monoxide (TiO);Ti 4 O 7 , Ti 5 O 9 This also includes titanium dioxide having an oxygen deficiency, as typified by the above.

[0031] In this specification, "titanium oxide" or "titania" refers to a compound having a terminal Ti-OH group, TiCOCH 3 Group, TiOCH 2 CH 3 Group, TiOCH 2 CH 2 CH 3 Group, TiOCH(CH 3 )CH 3 Group, TiOCH 2 CH 2 CH 2 CH 3 Group, TiOCOCH 3As typified by the above, the titanium oxide may partially contain groups other than Ti-O-Ti resulting from the synthesis of titanium oxide.

[0032] In this specification, "titanium oxide" or "titania" also includes those having an organic acid or the like bonded to a terminal OH group.

[0033] 1. Composite Nanoparticles The composite nanoparticles of the present invention are Lanthanum compounds, and Titania nanoparticles are included.

[0034] (1) Lanthanum compounds The lanthanum compound of the present invention is desirably water-soluble since it is to be composited with hydrophilic titania nanoparticles, but when the treatment is carried out in an organic solvent, a compound that is soluble in that solvent can be used.

[0035] The lanthanum compound is not particularly limited, but examples thereof include lanthanum acetate, lanthanum nitrate, lanthanum chloride, lanthanum acetylacetonate, lanthanum carbonate, lanthanum fluoride, lanthanum alkoxide, lanthanum trifluoromethanesulfonate, lanthanum oxalate, and lanthanum sulfate.

[0036] In the composite nanoparticles of the present invention, the lanthanum compound is preferably at least one lanthanum compound selected from the group consisting of lanthanum (III) acetate, lanthanum (III) acetate 1.5-hydrate, lanthanum (III) carbonate, lanthanum (III) carbonate octahydrate, lanthanum (III) oxide, lanthanum (III) nitrate, and lanthanum (III) nitrate hexahydrate.

[0037] Moreover, unnecessary materials such as lanthanum hydroxide and lanthanum oxide may be dissolved in an acid such as acetic acid or nitric acid and used.

[0038] (2) Titania nanoparticles The composite nanoparticles of the present invention containing titania nanoparticles and a lanthanum compound may be used as deodorant, antibacterial and antiviral materials.

[0039] The coexistence of lanthanum compounds with titania nanoparticles enhances the deodorizing, antibacterial and antiviral properties.

[0040] In the composite nanoparticle of the present invention, the content of the lanthanum compound is preferably 1% by mass to 25% by mass in terms of lanthanum atoms relative to the titania nanoparticle.

[0041] The mixing ratio of the titania nanoparticles and the lanthanum compound is not particularly limited, but is usually 1:0.001 to 1:1, and from the viewpoints of deodorizing, antibacterial, and antiviral properties and transparency, it is preferably 1:0.01 to 1:0.25.

[0042] The more lanthanum compounds are added, the greater the synergistic antibacterial and antiviral effect becomes; however, adding lanthanum compounds to highly transparent titania nanoparticles can decrease their transparency.

[0043] The titania nanoparticles preferably have a large specific surface area and high dispersibility in water.

[0044] The specific surface area of ​​titania nanoparticles is 10m 2 / g~500m 2 / g is preferred, 45m 2 / g~400m 2 / g is more preferable, and 90m 2 / g~350m 2 / g is more preferred.

[0045] The diameter of the titania nanoparticles is preferably from 1 nm to 150 nm, more preferably from 1 nm to 30 nm, further preferably from 1 nm to 16 nm, and most preferably from 1 nm to 6 nm.

[0046] In particular, the titania nanoparticles of the present invention are preferably those that are uniformly dispersed in water, and can be produced, for example, by the following production method.

[0047] (A) a step of mixing a titanium-containing substance, an organic acid, and water to obtain a dispersion; (B) stirring the dispersion obtained in the step (A) for 5 minutes or more; and (C) a step of heating the dispersion obtained in the step (B) at 70° C. or higher for 1 hour or more. and In the step (A), the mixture ratio of the titanium-containing substance and the organic acid is such that the amount of acyloxy groups in the organic acid is 0.4 mol or more per mol of titanium in the titanium-containing substance.

[0048] In the case of acetic acid, 2 moles or more is preferable, but in the case of lactic acid or citric acid, highly transparent titania nanoparticles can be obtained even with 0.5 moles or less.

[0049] <Process (A)> In step (A), a specific amount of a substance containing titanium, a specific amount of an organic acid, and water are mixed to obtain a dispersion.

[0050] The titanium-containing substance to be used is not particularly limited as long as it is a substance that becomes titanium oxide by heating. The titanium-containing substance is preferably titanium oxide and / or a titanium oxide precursor, and specifically includes titanium oxide; titanium hydroxide; titanium alkoxide; titanium halide such as titanium trichloride and titanium tetrachloride (particularly those neutralized with a base); metallic titanium, etc. Also, only one of these may be used, or two or more may be used in combination.

[0051] Among these, from the viewpoint of dispersibility of the obtained titania, titanium alkoxide, titanium hydroxide or titanium halide, particularly those neutralized with a base, are preferred, and titanium alkoxide is more preferred from the viewpoint of purity and dispersibility.

[0052] Examples of titanium alkoxides include titanium tetraisopropoxide, titanium tetra n-butoxide, titanium tetra n-propoxide, and titanium tetraethoxide. From the viewpoints of cost and water solubility of by-products, titanium tetraisopropoxide is preferred.

[0053] Depending on the combination of titanium alkoxide and organic acid, the resulting titania may act as a catalyst to liberate ester compounds that are poorly soluble in water, but the titania itself does not pose a problem. For example, when titanium tetra-n-butoxide and acetic acid are combined, butyl acetate is produced and liberated when they are mixed and heated.

[0054] From the viewpoint of obtaining a uniform dispersion, it is preferable to employ a combination of an organic acid and a titanium alkoxide that can provide an organic acid alkoxide having excellent water solubility.

[0055] Titanium halides (titanium tetrachloride, titanium trichloride, etc.) are preferably neutralized with a base and the precipitate washed from the viewpoints of impurities (halogens), corrosion of the reactor during mass production, and crystallinity control. In that case, it is preferable to use the titanium halides without drying from the viewpoint of dispersibility of the obtained titania.

[0056] When using a solid such as titanium oxide or metallic titanium, the average particle size is preferably 100 nm or less, more preferably 50 nm or less. The lower limit is not particularly set, but is usually about 1 nm. When the particle size is large, it may be ground in a dry or wet manner using a planetary ball mill, paint shaker, or the like. The average particle size can be measured, for example, by observation with an electron microscope (SEM or TEM).

[0057] The concentration of the titanium-containing substance in the dispersion is preferably 0.01 mol / L to 5 mol / L, and more preferably 0.05 mol / L to 3 mol / L, from the viewpoints of productivity and viscosity of the reaction liquid.

[0058] The acid used in the reaction is an organic acid, represented by the chemical formula C n H 2n+1 Monocarboxylic acids represented by COOH (n = 0-11), HOOCC m H 2m Examples thereof include dicarboxylic acids represented by COOH (m=0 to 8) and hydroxycarboxylic acids having 1 to 6 carbon atoms.

[0059] Of the monocarboxylic acids, acetic acid (n=1) is preferred from the viewpoints of solubility in water (especially those with n=4 or less are easily soluble in water) and odor (especially those with n=2 to 4 have a strong odor).

[0060] For the dicarboxylic acid, m is preferably 0 to 2 from the viewpoint of solubility in water, but m is more preferably 1 or 2 in consideration of dispersibility in titania.

[0061] Examples of hydroxycarboxylic acids include glycolic acid, lactic acid, malic acid, tartaric acid, and citric acid.

[0062] Of these, acetic acid and lactic acid are particularly preferred as the organic acid, from the viewpoint of being able to be removed later by volatilization.

[0063] These organic acids may be used alone or in combination of two or more.

[0064] From the viewpoints of dispersibility and cost, the amount of organic acid used is preferably adjusted so that the COOH group is contained in the titanium-containing substance in an amount of 0.4 mol or more, preferably 0.5 mol to 10 mol, per mol of titanium in the titanium-containing substance. The more organic acid is used, the more improved the dispersibility becomes.

[0065] The concentration of the organic acid in the dispersion is preferably from 0.005 mol / L to 10 mol / L, and more preferably from 0.02 mol / L to 7 mol / L, from the viewpoints of dispersibility and cost.

[0066] As the reaction solvent, it is preferable to use an aqueous solvent such as water as the main component (specifically, for example, 50% by weight or more), but alcohols or esters may be contained during the reaction.

[0067] When titanium tetraisopropoxide is used as a raw material, it reacts with organic acids to produce isopropanol, and may also produce isopropyl esters of organic acids upon heating.

[0068] Alcohols or esters may be added to the dispersion obtained in step (A) or may be generated in the system. The alcohols or esters may be removed by heating in an open system at 100° C. or less, or may remain in the reaction liquid.

[0069] When an alcohol is contained in the dispersion liquid, the particle size tends to become small, and therefore, in order to control the particle size, an alcohol may be intentionally added.

[0070] In the present invention, inorganic acids (particularly strong inorganic acids) such as nitric acid, hydrochloric acid, and sulfuric acid, which are often used in hydrothermal synthesis reactions of titania nanoparticles, may be used. Carboxylic acids are preferred from the viewpoints of corrosion of the equipment, impurities, wastewater, etc., in addition to the low adhesion of the resulting titania nanoparticles to the substrate.

[0071] Inorganic and organic acids can be used supplementarily to improve the dispersibility and uniformity of the raw material and to facilitate handling, without impairing the effect, for example, in the range of 0.01 mol / L or less. In this case, the concentrations of N, Cl, and S elements in the dispersion liquid are all 0.01 mol / L.

[0072] Of the inorganic acids and organic acids, nitric acid is preferred because it easily produces anatase-type titania, which has high transparency, and is easy to remove.

[0073] The pH of the dispersion obtained in such step (A) is preferably at least pH 1.5 and less than pH 6, more preferably pH 2 to pH 5, from the viewpoints of corrosion of the equipment, safety in handling, and dispersibility.

[0074] In step (A), the method for preparing the dispersion is not particularly limited, and the titanium-containing substance, the organic acid, and water (solvent) may be mixed simultaneously or successively. In particular, from the viewpoint of preventing aggregation and forming large lumps and enabling continuous stirring, it is preferable to mix the organic acid and water (solvent) and then add the titanium-containing substance while stirring.

[0075] On the other hand, if water is added dropwise to a mixture of a titanium-containing substance and an organic acid, the mixture is more likely to aggregate.

[0076] <Process (B)> In the step (B), the dispersion obtained in the step (A) is stirred for 5 minutes or more.

[0077] The stirring method is not particularly limited, and may be performed according to a conventional method. The stirring time is 5 minutes or more, preferably 15 minutes or more, from the viewpoint of sufficiently reacting the titanium-containing substance with the organic acid and water. The upper limit of the stirring time is not particularly limited, but is usually about 240 hours.

[0078] <Process (C)> In the step (C), the dispersion obtained in the step (B) is heated at 70° C. or higher for 1 hour or more.

[0079] Step (C) may be carried out under normal pressure or under pressure in a closed vessel.

[0080] When heating is performed under pressure, it may be performed under supercritical conditions. More specifically, the pressure during heating is preferably 0.45 MPa or more, more preferably 1 MPa to 30 MPa, from the viewpoint of increasing the particle size. However, when a small particle size is acceptable, it is easier to perform the heating under normal pressure.

[0081] The heating temperature is 50° C. or higher, preferably 70° C. to 450° C., and more preferably 150° C. to 400° C. If the heating temperature is less than 50° C., highly active titania nanoparticles cannot be obtained.

[0082] When the reaction is carried out under normal pressure, the reaction temperature is preferably 50° C. to 120° C., and more preferably 70° C. to 110° C., from the viewpoint of obtaining titania nanoparticles having a smaller average particle size.

[0083] When the reaction is carried out under pressure (not supercritical), from the viewpoint of obtaining titania nanoparticles having a larger average particle size than those under normal pressure, the temperature is preferably 120° C. to 370° C., more preferably 150° C. to 300° C. In this case, the reaction may be first heated at a low temperature (e.g., 50° C. to 120° C.) and then heated to a high temperature (e.g., 120° C. to 370° C.).

[0084] When the reaction is carried out under supercritical conditions, even under pressure, the dispersion obtained in step (B) can be mixed with supercritical water in a flow reactor, for example, to synthesize titania nanoparticles with uniform particle size and a titania dispersion with extremely high dispersibility in an extremely short time. In this case, it is preferable to mix the dispersion obtained in step (B) at 50°C or less with supercritical water at 374°C or more and hold it at 300°C or more (particularly 375°C to 450°C) for 1 second or more (particularly 5 seconds to 600 seconds). When contacting with supercritical water, the reaction can be completed in an extremely short time.

[0085] The titania nanoparticles of the present invention thus obtained have significantly improved dispersibility compared to conventional titania nanoparticles.

[0086] In the composite nanoparticles of the present invention, the titania nanoparticles preferably have an average particle size of 30 nm or less.

[0087] The titania nanoparticles of the present invention have an average particle size of about 3 nm to 50 nm, and particularly about 4 nm to 40 nm.

[0088] By setting the average particle size of the titania nanoparticles within this range, it is possible to support the metal nanoparticles appropriately and more firmly, and a film having higher visible light catalytic activity and dark catalytic activity and higher transparency can be formed.

[0089] Normally, when the average particle size is small, the shrinkage during heating is large, which makes it easy for cracks and peeling off from the substrate to occur. However, the metal nanoparticle-supported titania nanoparticles of the present invention are a material with excellent coatability, despite the use of titania nanoparticles with a small average particle size.

[0090] In the present invention, the average particle size of the titania nanoparticles is measured by observation with a transmission electron microscope (TEM).

[0091] In the composite nanoparticle of the present invention, preferably, the titania nanoparticle has an acyloxy group bonded to at least a part of the titanium atoms present on the surface, and has a specific surface area of ​​70 m 2 / g or more.

[0092] The titania nanoparticles of the present invention have a specific surface area of ​​30 m 2 / g~500m 2 / g, especially 40m 2 / g~350m 2 / g is obtained.

[0093] By setting the specific surface area of ​​the titania nanoparticles within this range, the metal nanoparticles can be supported appropriately and more firmly, and the visible light catalytic activity and the dark catalytic activity can be easily increased.

[0094] The specific surface area of ​​the titania nanoparticles is measured by the BET method.

[0095] The titania nanoparticles of the present invention have N, Cl, and S element concentrations of 0 to 5,000 ppm, and particularly 0 to 1,000 ppm.

[0096] By setting the concentrations of N, Cl, and S elements in the titania nanoparticles within this range, corrosion of the substrate can be easily suppressed. 4 , TiOSO 4 This means that impurities derived from acidic titania precursors such as tungsten, tungsten oxide, and the like are absent or present in only small amounts.

[0097] The concentrations of N, Cl, and S elements in the titania nanoparticles are measured by WDX (fluorescent X-ray).

[0098] The crystal form of the titania nanoparticles is preferably anatase type, which can particularly improve the visible light catalytic activity and the dark catalytic activity.

[0099] There are no other crystal forms than the anatase type, and it is preferable that the anatase type is 100%.

[0100] Thereafter, the titania nanoparticles of the present invention can be recovered by precipitating and centrifuging the titania nanoparticles of the present invention using a conventional method.

[0101] In this way, the titania nanoparticles of the present invention can be used for a wide variety of purposes, including not only photocatalysis (superhydrophilicity, decomposition of organic / inorganic matter, hydrogen production, etc.), but also dye-sensitized solar cells, transparent conductive films, catalyst supports, heat-resistant coatings, high refractive coatings, and heat-shielding coatings, because the average particle size and specific surface area of ​​the titania nanoparticles can be adjusted and they have excellent dispersibility.

[0102] The titania dispersion used in the present invention can be made uniform by using the reaction liquid that has been subjected to the above steps (A) to (C) and adding a dispersion step such as ultrasonic dispersion.

[0103] In the composite nanoparticles of the present invention, preferably, when the titania nanoparticles are heated up to 600° C. using a simultaneous differential thermal and thermogravimetric analyzer, the weight loss at 200° C. or higher is 5% by mass or more.

[0104] In the present invention, the form of metal nanoparticles (lanthanum compound) supported titania nanoparticles is preferably adopted, and metal nanoparticle-supported titania nanoparticles in which metal nanoparticles are supported on the surface of titania nanoparticles are preferred.

[0105] In the present invention, the titania nanoparticles preferably have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and metal nanoparticles are supported on the surface in an amount of 90 mass% or less relative to the titanium oxide in the titania nanoparticles.

[0106] In the present invention, preferably, when the temperature is raised to 600° C. using a thermogravimetric and differential thermal analyzer, the mass loss at 200° C. or higher is 5% by mass or more.

[0107] In the metal nanoparticle (lanthanum compound)-supported titania nanoparticles of the present invention, the average particle size and specific surface area of ​​both the titania nanoparticles and the metal nanoparticles can be adjusted, and the titania nanoparticles and the metal nanoparticles are firmly adhered to each other. In addition, the titania nanoparticles and the metal nanoparticles have excellent dispersibility and are not prone to aggregation, so that the metal nanoparticles have excellent coatability and transparency without the need for additional additives such as dispersants.

[0108] The metal nanoparticle (lanthanum compound)-supported titania nanoparticles and photocatalyst of the present invention have sufficient coatability and transparency without the use of a separate dispersant, and therefore can have excellent visible light catalytic activity without the visible light catalytic activity being impaired by additives such as dispersants.

[0109] The metal nanoparticle (lanthanum compound)-supported titania nanoparticle of the present invention is a visible light responsive photocatalyst, particularly a photocatalyst that is useful even in the dark.

[0110] Generally, water, inorganic acids, free organic acids, etc. volatilize almost entirely at temperatures below 200°C.

[0111] The titania nanoparticles constituting the metal nanoparticle (lanthanum compound)-supported titania nanoparticles of the present invention have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and therefore the acyloxy groups are gradually eliminated in the range of 200° C. to 600° C. For example, in the case of acetoxy groups, the acetoxy groups are gradually eliminated in the range of 200° C. to 600° C., with a peak at about 260° C.

[0112] The titania nanoparticles constituting the metal nanoparticle (lanthanum compound)-supported titania nanoparticles of the present invention have acyloxy groups bonded to at least some of the titanium atoms present on the surface, which makes it possible to suppress aggregation of the titania nanoparticles during drying or firing, making them less susceptible to cracking, peeling, and the like. As a result, the titania nanoparticles are particularly excellent in coatability and transparency, and cracking, peeling, and the like can be suppressed. Furthermore, the metal nanoparticles described below can be easily firmly supported, resulting in excellent visible light catalytic activity.

[0113] It is generally known in the art that the presence of acyloxy groups on the surface generally reduces visible light catalytic activity.

[0114] In the present invention, the aggregation of titania nanoparticles during drying or calcination can be suppressed, so that the effect of suppressing cracks, peeling, etc. is particularly excellent. In addition, since it is easy to firmly support metal nanoparticles (lanthanum compounds), it is possible to improve visible light catalytic activity despite the presence of acyloxy groups.

[0115] Titania nanoparticles preferably have a large number of acyloxy groups bonded to titanium atoms present on the surface. When acyloxy groups are present on at least some of the titanium atoms present on the surface, they are gradually released in the range of 200°C to 600°C, and therefore, when the temperature is increased using a thermogravimetric and differential thermal analyzer (TG-DTA), the mass loss is large at temperatures above 200°C.

[0116] In the present invention, when the temperature is increased using a thermogravimetry-differential thermal analyzer (TG-DTA), the mass loss at 200°C or higher represents an index of the number of acetoxy groups bonded to titanium atoms present on the surface.

[0117] When heated to 600° C. using a thermogravimetry and differential thermal analyzer (TG-DTA), the mass loss at 200° C. or higher is 5% by mass or more, preferably 7% by mass to 20% by mass. The detailed conditions for the thermogravimetry and differential thermal analyzer (TG-DTA) are as follows: atmosphere: air, heating rate: 3° C. / min.

[0118] Titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and these acyloxy groups are preferably bonded to the titanium atoms via a group represented by -OCOR (wherein R represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a hydroxyalkyl group having 1 to 2 carbon atoms).The acyloxy group is preferably an acyloxy group derived from an organic acid such as a monocarboxylic acid having 1 to 4 carbon atoms or a hydroxycarboxylic acid having 2 to 3 carbon atoms.

[0119] In the above R, preferred examples of the alkyl group include a methyl group, an ethyl group, and an n-propyl group.

[0120] In the above R, preferred examples of the hydroxyalkyl group include a hydroxymethyl group, a 1-hydroxyethyl group, and a 2-hydroxyethyl group.

[0121] Preferred examples of the monocarboxylic acid include formic acid, acetic acid, propionic acid, and butyric acid. Preferred examples of the hydroxycarboxylic acid include glycolic acid and lactic acid.

[0122] From the viewpoints of volatility, harmfulness and decomposability, R is preferably a hydrogen atom, or a methyl group, a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, or the like, and from the viewpoints of water solubility and odor, a methyl group is preferred.

[0123] From the viewpoints of volatility, harmfulness and decomposability, the monocarboxylic acid is preferably formic acid, acetic acid, etc., and the hydroxycarboxylic acid is preferably glycolic acid, lactic acid, etc.

[0124] Acetic acid is particularly preferred from the viewpoints of water solubility and odor.

[0125] The organic acids can be used alone or in combination of two or more kinds.

[0126] In conventional titania dispersions, it was impossible to obtain a uniform dispersion unless a dispersing agent was used.

[0127] In the present invention, a dispersant may be added, but even without adding a dispersant, a dispersion liquid with far better dispersibility than that of normal titania nanoparticles can be obtained. As a result of the good dispersibility, the crack resistance of the coating is also excellent.

[0128] No dispersant is required, resulting in a dense titania coating.

[0129] In this case, in the titania dispersion of the present invention, the content of water as a solvent is preferably 60% by weight or more, particularly 75% by weight or more, from the viewpoints of ease of coating and film properties of the coating.

[0130] It is also possible to take out titania nanoparticles from the reaction solution and change the solvent. Water may be removed from the reaction solution by centrifugation or a filtration membrane, and the water may be replaced with an organic solvent. In this case, it is preferable not to dry the titania nanoparticles from the viewpoints of dispersibility, transparency, etc.

[0131] Examples of the organic solvent used in the dispersion include alcohols, etc. Examples of the alcohols include aliphatic alcohols having 1 to 6 carbon atoms, such as methanol, ethanol, and isopropanol, as well as non-aliphatic alcohols, such as α-terpineol, glycol solvents, such as butyl carbitol (diethylene glycol monobutyl ether), hexylene glycol (2-methyl-2,4-pentanediol), ethylene glycol-2-ethylhexyl ether, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether, and diols, such as 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.

[0132] The organic solvent used in the dispersion may not have an OH group, as long as it has affinity with titania and other solvents (water, alcohol, etc.), and examples of the organic solvent include diethylene glycol butyl methyl ether, tripropylene glycol dimethyl ether, triethylene glycol dimethyl ether, diethylene glycol dibutyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol diacetate, triethylene glycol diacetate, tetraethylene glycol diacetate, etc. Among these, diethylene glycol monobutyl ether acetate, tetraethylene glycol dimethyl ether, etc. are preferred from the viewpoint of boiling point, etc.

[0133] 2. Manufacturing method of composite nanoparticles The method for producing the composite nanoparticles of the present invention comprises the steps of: The composite nanoparticles contain a lanthanum compound and a titania nanoparticle, The method includes a step of mixing titania and a lanthanum compound in a solvent containing at least water.

[0134] In the method for producing composite nanoparticles of the present invention, the lanthanum compound is preferably at least one lanthanum compound selected from the group consisting of lanthanum (III) acetate, lanthanum (III) acetate 1.5hydrate, lanthanum (III) carbonate, lanthanum (III) carbonate octahydrate, lanthanum (III) oxide, lanthanum (III) nitrate, and lanthanum (III) nitrate hexahydrate.

[0135] 3. Deodorizing, antibacterial and / or antiviral materials and antiviral coating solutions The deodorizing, antibacterial, and / or antiviral material of the present invention has the following properties: Contains a lanthanum compound and titania nanoparticles, The titania nanoparticles have an average particle size of 30 nm or less.

[0136] The deodorizing, antibacterial, and / or antiviral material of the present invention preferably further contains at least one metal selected from the group consisting of silver, copper, platinum, and zinc.

[0137] The antiviral coating liquid of the present invention contains the deodorizing, antibacterial, and / or antiviral material and water.

[0138] The viscosity of the antiviral coating liquid of the present invention is adjusted depending on the application. For example, when it is used for spin coating, dip coating, spraying, or the like, it is adjusted to a low viscosity.

[0139] When the antiviral coating liquid of the present invention is used for brush application, squeegee method, or the like, the viscosity is adjusted to be higher.

[0140] When the antiviral coating liquid of the present invention is used for screen printing, it is preferable to adjust the viscosity to be higher and suppress the fluidity.

[0141] The coating of the present invention is a dense coating. EXAMPLES

[0142] The present invention will now be described in detail with reference to examples.

[0143] The present invention is not limited to these.

[0144] [Example 1] 120 g (2 mol) of acetic acid was added to 142.1 g (0.5 mol) of titanium tetraisopropoxide and stirred for 15 minutes, and then 550 g of water was added. The pH of this dispersion was 2.5.

[0145] A large amount of translucent precipitate was generated, but after stirring for 60 minutes and heating at 60°C, the precipitate was completely dissolved.

[0146] After that, the mixture was stirred at normal pressure (0.1 MPa) at 80°C for 5 hours, and then water was added to the reaction liquid to make a total of 800 g. After that, ultrasonic waves were applied to the mixture, and a translucent, uniform titania dispersion was obtained without using a strong inorganic acid.

[0147] 50 g of water was added to 50 g of this titania dispersion, and 0.309 g of lanthanum acetate 1.5 hydrate (titania:lanthanum atom = 1:0.05) (5 mass% as lanthanum atom relative to the titania nanoparticles) was further added and ultrasonic dispersion was performed, resulting in a white, uniform dispersion.

[0148] This dispersion was spin-coated onto a glass substrate at 1,000 rpm for 60 seconds, resulting in a uniform, colorless coating.

[0149] [Example 2] A test was carried out in the same manner as in Example 1, except that the amount of lanthanum acetate was 0.618 g (titania:lanthanum atom=1:0.1) (10 mass % as lanthanum atom relative to the titania nanoparticles).

[0150] This dispersion was spin-coated onto a glass substrate at 1,000 rpm for 60 seconds, resulting in a uniform, colorless coating.

[0151] [Example 3] 120g (2mol) of acetic acid was added to 142.1g (0.5mol) of titanium tetraisopropoxide, and the mixture was stirred for 15 minutes, and 550g of water was added. The pH of this dispersion was 2.5. A large amount of translucent precipitate was generated, but after stirring for 60 minutes and heating, the precipitate was completely dissolved at 60℃.

[0152] After that, the mixture was stirred at normal pressure (0.1 MPa) at 80°C for 5 hours, and then water was added to the reaction liquid to make a total of 800 g. After that, ultrasonic waves were applied to the mixture, and a translucent, uniform titania dispersion was obtained without using a strong inorganic acid.

[0153] 10g of water was added to 10g of this titania dispersion, and 0.108g of lanthanum carbonate octahydrate (titania:lanthanum atom = 1:0.05) (5% by mass of lanthanum atom relative to titania nanoparticles) was added and stirred, resulting in a white precipitate. Dissolution occurred after stirring for 1 hour. Ultrasonic dispersion was performed, resulting in a white, uniform dispersion.

[0154] This dispersion was spin-coated onto a glass substrate at 1,000 rpm for 60 seconds, resulting in a uniform, colorless coating.

[0155] [Example 4] A test was carried out in the same manner as in Example 3, except that lanthanum carbonate was replaced with 0.0586 g of lanthanum oxide (titania:lanthanum atom = 1:0.05) (5 mass % as lanthanum atom relative to titania nanoparticles). A white precipitate was observed, but it was dissolved by stirring for 1 hour. After ultrasonic dispersion, a white uniform dispersion was obtained.

[0156] This dispersion was spin-coated onto a glass substrate at 1,000 rpm for 60 seconds, resulting in a uniform, colorless coating.

[0157] [Example 5] A test was carried out in the same manner as in Example 3, except that lanthanum carbonate was replaced with 0.0779 g of lanthanum nitrate hexahydrate (titania:lanthanum atom=1:0.05) (5 mass % as lanthanum atom relative to titania nanoparticles).

[0158] After ultrasonic dispersion, a white, semi-transparent, uniform dispersion was obtained.

[0159] This dispersion was spin-coated onto a glass substrate at 1,000 rpm for 60 seconds, yielding a transparent, colorless coating.

[0160] [Example 6] 120g (2mol) of acetic acid was added to 142.1g (0.5mol) of titanium tetraisopropoxide and stirred for 15 minutes, and 550g of water was added. The pH of this dispersion was 2.5. A large amount of translucent precipitate was generated. After stirring for 60 minutes, the mixture was heated to 60°C, at which point all of the precipitate dissolved.

[0161] After that, the mixture was stirred at normal pressure (0.1 MPa) at 80°C for 5 hours, and then water was added to the reaction liquid to make a total of 800 g. After that, ultrasonic waves were applied to the mixture, and a translucent, uniform titania dispersion was obtained without using a strong inorganic acid.

[0162] 0.0484 g of silver acetate was added to 12.5 g of this dispersion containing 5 wt % titania and 12.5 g of water, and the mixture was stirred and subjected to ultrasonic dispersion, whereby a uniform dispersion was obtained.

[0163] 0.39 g of lanthanum nitrate hexahydrate (titania:lanthanum atom = 1:0.2) (20 mass % as lanthanum atom relative to titania nanoparticles) was added to the obtained liquid, stirred, and subjected to ultrasonic dispersion, resulting in a uniform dispersion.

[0164] This dispersion was spin-coated three times on a glass substrate at 500 rpm for 30 seconds, resulting in a uniform, colorless coating.

[0165] The antiviral properties of this test piece were evaluated using feline coronavirus in accordance with JIS R 1756. However, the test was conducted in the dark, without exposure to light (conditions: 8 hours). As a result, 87% of the virus was inactivated with this material, compared to a material that was not coated with this material.

[0166] [Comparative Example 1] When 5.25 g of lanthanum acetate sesquihydrate was mixed with 95 g of water, a clear solution was obtained.

[0167] This dispersion was spin-coated onto a glass substrate at 500 rpm for 30 seconds. When dried, it became cloudy and uneven, and was not uniform.

[0168] [Comparative Example 2] When 5.25 g of lanthanum acetate sesquihydrate was mixed with 95 g of water, a clear solution was obtained.

[0169] This solution was heated to 80°C over 4.5 hours with stirring, then further heated to 90°C over 1 hour, and after maintaining this temperature for 1.5 hours the solution became cloudy, and after leaving it to stand for 24 hours a precipitate formed.

[0170] This liquid was spin-coated onto a glass substrate at 500 rpm for 30 seconds, but when it dried it became cloudy and uneven, and the coating was not uniform.

[0171] [Comparative Example 3] When 5.25 g of lanthanum acetate sesquihydrate was mixed with 95 g of water, a clear solution was obtained.

[0172] When 2 g of 25% aqueous ammonia was added to this solution, the liquid became cloudy, but when left to stand, the supernatant separated and the liquid did not become homogeneous.

[0173] This liquid was spin-coated onto a glass substrate at 500 rpm for 30 seconds, but when it dried it became cloudy and uneven, and the coating was not uniform.

[0174] As such, it has been difficult to coat lanthanum compounds uniformly or to form them into nanoparticles by simple operations.

[0175] [Comparative Example 4] 120g (2mol) of acetic acid was added to 142.1g (0.5mol) of titanium tetraisopropoxide, and the mixture was stirred for 15 minutes, and 550g of water was added. The pH of this dispersion was 2.5. A large amount of translucent precipitate was generated, but after stirring for 60 minutes and heating, the precipitate was completely dissolved at 60℃.

[0176] After that, the mixture was stirred at normal pressure (0.1 MPa) at 80°C for 5 hours, and then water was added to the reaction liquid to make a total of 800 g. After that, ultrasonic waves were applied to the mixture, and a translucent, uniform titania dispersion was obtained without using a strong inorganic acid.

[0177] 10 g of this dispersion containing 5 wt % titania and 0.039 g of silver acetate were added and stirred, and ultrasonic dispersion was performed, whereby a uniform dispersion was obtained (titania:silver atom=1:0.05).

[0178] This dispersion was spin-coated three times on a glass substrate at 500 rpm for 30 seconds, resulting in a uniform, colorless coating.

[0179] The antiviral properties of this test piece were evaluated using feline coronavirus according to the method of JIS R 1756. However, the test was conducted in a dark place without exposure to light (conditions: × 8 hours). As a result, inactivation of the virus could not be confirmed.

[0180] [Comparative Example 5] 120g (2mol) of acetic acid was added to 142.1g (0.5mol) of titanium tetraisopropoxide and stirred for 15 minutes, and 550g of water was added. The pH of this dispersion was 2.5. A large amount of translucent precipitate was generated. After stirring for 60 minutes, the mixture was heated to 60°C, at which point all of the precipitate dissolved.

[0181] After that, the mixture was stirred at normal pressure (0.1 MPa) at 80°C for 5 hours, and then water was added to the reaction liquid to make a total of 800 g. After that, ultrasonic waves were applied to the mixture, and a translucent, uniform titania dispersion was obtained without using a strong inorganic acid.

[0182] 12.5 g of this dispersion containing 5 wt % titania, 12.5 g of water, 0.0313 g of an aqueous solution of chloroplatinic acid, and 0.3 g of triethoxysilane were added and stirred, and ultrasonic dispersion was performed to obtain a uniform dispersion.

[0183] This dispersion was spin-coated three times at 500 rpm for 30 seconds, resulting in a uniform, colorless coating.

[0184] The antiviral properties of this test piece were evaluated using feline coronavirus according to the method of JIS R 1756. However, the test was conducted in a dark place without exposure to light (conditions: × 8 hours). As a result, inactivation of the virus could not be confirmed.

[0185] [Comparative Example 6] 120g (2mol) of acetic acid was added to 142.1g (0.5mol) of titanium tetraisopropoxide and stirred for 15 minutes, and 550g of water was added. The pH of this dispersion was 2.5. A large amount of translucent precipitate was generated. After stirring for 60 minutes, the mixture was heated to 60°C, at which point all of the precipitate dissolved.

[0186] After that, the mixture was stirred at normal pressure (0.1 MPa) at 80°C for 5 hours, and then water was added to the reaction liquid to make a total of 800 g. After that, ultrasonic waves were applied to the mixture, and a translucent, uniform titania dispersion was obtained without using a strong inorganic acid.

[0187] 12.5 g of this dispersion containing 5 wt % titania, 12.5 g of water, and 0.039 g of silver acetate were added and stirred, and ultrasonic dispersion was performed to obtain a uniform dispersion.

[0188] Separately, 12.5 g of this dispersion containing 5 wt % titania, 12.5 g of water, 0.0313 g of an aqueous solution of chloroplatinic acid, and 0.3 g of triethoxysilane were added and stirred, and ultrasonic dispersion was performed to obtain a uniform dispersion.

[0189] The above two types of dispersion liquid were mixed and subjected to ultrasonic dispersion, whereby a uniform dispersion liquid was obtained (titania:silver atom:platinum atom=1:2.5:0.025).

[0190] This dispersion was spin-coated three times at 500 rpm for 30 seconds, resulting in a uniform, colorless coating.

[0191] The antiviral properties of this test piece were evaluated using feline coronavirus according to the method of JIS R 1756. However, the test was conducted in a dark place without exposure to light (conditions: × 8 hours). As a result, inactivation of the virus could not be confirmed.

Claims

1. A composite nanoparticle, Lanthanum compounds, and Titania nanoparticles, the lanthanum compound is at least one lanthanum compound selected from the group consisting of lanthanum(III) acetate, lanthanum(III) acetate 1.5-hydrate, lanthanum(III) carbonate, lanthanum(III) carbonate octahydrate, lanthanum(III) oxide, lanthanum(III) nitrate, and lanthanum(III) nitrate hexahydrate; The titania nanoparticles are anatase type titania, The titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and have a specific surface area of ​​70 m 2 / g or more, the average particle size of the particles is 1 nm to 6 nm in diameter, The lanthanum compound is supported on the surface of the titania nanoparticles, The content of the lanthanum compound is 1% by mass to 25% by mass in terms of lanthanum atoms relative to the titania nanoparticles. Composite nanoparticles.

2. 2. The composite nanoparticle according to claim 1, wherein the titania nanoparticles undergo a weight loss of 5% by mass or more at 200° C. or higher when heated to 600° C. using a thermogravimetric and differential thermal analyzer.

3. A method for producing composite nanoparticles, comprising the steps of: The composite nanoparticles contain a lanthanum compound and a titania nanoparticle, the lanthanum compound is at least one lanthanum compound selected from the group consisting of lanthanum(III) acetate, lanthanum(III) acetate 1.5-hydrate, lanthanum(III) carbonate, lanthanum(III) carbonate octahydrate, lanthanum(III) oxide, lanthanum(III) nitrate, and lanthanum(III) nitrate hexahydrate; The titania nanoparticles are anatase type titania, The method includes a step of mixing an organic acid, the titania, and the lanthanum compound in a solvent containing at least water, In the composite nanoparticles, The titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and have a specific surface area of ​​70 m 2 / g or more, the average particle size of the particles is 1 nm to 6 nm in diameter, The lanthanum compound is supported on the surface of the titania nanoparticles, The content of the lanthanum compound is 1% by mass to 25% by mass in terms of lanthanum atoms relative to the titania nanoparticles. Manufacturing method.

4. A deodorant material, an antibacterial material, or an antiviral material, The present invention relates to a method for producing a lanthanum-based nanoparticle-based composite material comprising: the lanthanum compound is at least one lanthanum compound selected from the group consisting of lanthanum(III) acetate, lanthanum(III) acetate 1.5-hydrate, lanthanum(III) carbonate, lanthanum(III) carbonate octahydrate, lanthanum(III) oxide, lanthanum(III) nitrate, and lanthanum(III) nitrate hexahydrate; The titania nanoparticles are anatase type titania, The titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and have a specific surface area of ​​70 m 2 / g or more, the average particle size of the particles is 1 nm to 6 nm in diameter, The lanthanum compound is supported on the surface of the titania nanoparticles, The content of the lanthanum compound is 1% by mass to 25% by mass in terms of lanthanum atoms relative to the titania nanoparticles. Deodorizing, antibacterial, or antiviral materials.

5. 5. The deodorizing, antibacterial, or antiviral material according to claim 4, further comprising at least one metal selected from the group consisting of silver, copper, platinum, and zinc.

6. An antiviral coating solution, The deodorizing material, antibacterial material, or antiviral material according to claim 4 or 5, and Contains water Antiviral coating liquid.

Citation Information

Patent Citations

  • Photocatalyst body and its production

    JP1998174881A

  • Method and device for exhaust gas treatment

    JP2003159514A

  • Method for manufacturing mixed oxide having average particle size of less than 10 nanometer

    JP2005001988A

  • Composition for forming solid electrolyte layer, method for forming solid electrolyte layer, solid electrolyte layer, and lithium ion secondary battery

    JP2013105646A

  • Titania nanoparticle, dispersion liquid thereof, and titania paste using the titania nanoparticle

    JP2014201451A